IS THE RIGHT TO DIE WITH DIGNITY CONSTITUTIONALLY GUARANTEED? BAXTER V MONTANA* AND OTHER DEVELOPMENTS IN PATIENT AUTONOMY AND PHYSICIAN ASSISTED SUICIDE - Suhayfa Bhamjee (Obiter, 2021)
This article examines the question of whether the right to life encompasses the right to die with dignity. It looks at the concepts of autonomy and paternalism as they exist as major themes on either side of the debate. Physician Assisted Suicide (Voluntary Euthanasia) has come under the spotlight in several jurisdictions, not just our own. Most recently in Montana, USA, the issue came before the Supreme Court for deliberation. The states of Washington and Oregon have legislations specific to PAS, legitimizing assisted suicide and removing wrongfulness from the actions of a physician who assists in the prescribed manner. Montana does not have specific legislation, but instead relied on the clauses of its Constitution, and it was held that the right to die with dignity is constitutionally guaranteed in that state. Here, argument is made suggesting that the right to die with dignity, in other words, to seek and easy passing through PAS, is also guaranteed in our Constitution.